2019
DOI: 10.29289/2594539420190000371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of local recurrence of breast conservation surgery at the Ceará Institute of Cancer

Abstract: O câncer de mama é o tumor maligno que mais acomete mulheres em todo o mundo, excetuando-se os casos de pele não melanoma. No Brasil, estimavam-se mais de 56.000 casos para 2016. A mortalidade esperada ainda é alta devido ao diagnóstico tardio. Na atualidade, a cirurgia conservadora é o padrão-ouro. Objetivo: Avaliar a recidiva locorregional da cirurgia conservadora praticada no Instituto do Câncer do Ceará, no período entre 2002 a 2012. Método: Estudo transversal e descritivo, utilizando dados secundários obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In our study, it was 40 to 49 years of age. In an analysis carried out by Magalhães et al 20 , distant metastasis was observed in 3.1% of the sample, and locoregional metastasis, in 0.6%, corroborating the findings of our study, in which distant metastasis was found in 13.58% of the patients, and rates of 4.8% more chances of this type of metastasis in patients aged less than 50, and 4% among patients with locoregional metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, it was 40 to 49 years of age. In an analysis carried out by Magalhães et al 20 , distant metastasis was observed in 3.1% of the sample, and locoregional metastasis, in 0.6%, corroborating the findings of our study, in which distant metastasis was found in 13.58% of the patients, and rates of 4.8% more chances of this type of metastasis in patients aged less than 50, and 4% among patients with locoregional metastasis.…”
Section: Discussionsupporting
confidence: 92%